A systems level analysis reveals transcriptomic and proteomic complexity in Ixodes ricinus midgut and salivary glands during early attachment and feeding - Schwarz, Alexandra; Tenzer, Stefan; Hackenberg, Michael; Erhart, Jan; Gerhold-Ay, Aslihan; Mazur, Johanna; Kuharev, Jörg; Ribeiro, José M C; Kotsyfakis, Michail (Molecular & cellular proteomics, 2014)
Although pathogens are usually transmitted within the first 24-48 h of attachment of the castor bean tick Ixodes ricinus, little is known about the tick's biological responses at these earliest phases of attachment. Tick midgut and salivary glands are the main tissues involved in tick blood feeding and pathogen transmission but the limited genomic information for I. ricinus delays the application of high-throughput methods to study their physiology. We took advantage of the latest advances in the fields of Next Generation RNA-Sequencing and Label-free Quantitative Proteomics to deliver an unprecedented, quantitative description of the gene expression dynamics in the midgut and salivary glands of this disease vector upon attachment to the vertebrate host. A total of 373 of 1510 identified proteins had higher expression in the salivary glands, but only 110 had correspondingly high transcript levels in the same tissue. Furthermore, there was midgut-specific expression of 217 genes at both the transcriptome and proteome level. Tissue-dependent transcript, but not protein, accumulation was revealed for 552 of 885 genes. Moreover, we discovered the enrichment of tick salivary glands in proteins involved in gene transcription and translation, which agrees with the secretory role of this tissue; this finding also agrees with our finding of lower tick t-RNA representation in the salivary glands when compared with the midgut. The midgut, in turn, is enriched in metabolic components and proteins that support its mechanical integrity in order to accommodate and metabolize the ingested blood. Beyond understanding the physiological events that support hematophagy by arthropod ectoparasites, we discovered more than 1500 proteins located at the interface between ticks, the vertebrate host, and the tick-borne pathogens. Thus, our work significantly improves the knowledge of the genetics underlying the transmission lifecycle of this tick species, which is an essential step for developing alternative methods to better control tick-borne diseases.
Keywords: stadia vývoje; Ixodes; RNA, Transfer; regulace genové exprese; Proteomics; Molecular Sequence Data; molekulární sekvence - údaje; Female; Organ Specificity; Salivary Glands; klíště; zvířata; proteomika; RNA transferová; ženské pohlaví; Gene Expression Regulation; Male; stanovení celkové genové exprese; slinné žlázy; Life Cycle Stages; Animals; Gene Expression Profiling; mužské pohlaví; Gastrointestinal Tract; orgánová specificita; gastrointestinální trakt